Multimodal Imaging and Analysis of the Neuroanatomical Organization of the Primary Olfactory Inputs in the Brownbanded Bamboo Shark, Chiloscyllium punctatum - Camilieri-Asch, Victoria; Caddy, Harrison T.; Hubbard, Alysia; Rigby, Paul; Doyle, Barry; Shaw, Jeremy A.; Mehnert, Andrew; Partridge, Julian C.; Yopak, Kara E.; Collin, Shaun P. (Frontiers in Neuroanatomy, 2020)
There is currently a limited understanding of the morphological and functional organization of the olfactory system in cartilaginous fishes, particularly when compared to bony fishes and terrestrial vertebrates. In this fish group, there is a clear paucity of information on the characterization, density, and distribution of olfactory receptor neurons (ORNs) within the sensory olfactory epithelium lining the paired olfactory rosettes, and their functional implications with respect to the hydrodynamics of incurrent water flow into the nares. This imaging study examines the brownbanded bamboo shark Chiloscyllium punctatum (Elasmobranchii) and combines immunohistochemical labeling using antisera raised against five G-protein α-subunits (Gαs/olf, Gαq/11/14, Gαi–1/2/3, Gαi–3, Gαo) with light and electron microscopy, to characterize the morphological ORN types present. Three main ORNs (“long”, “microvillous” and “crypt-like”) are confirmed and up to three additional microvilli-bearing types are also described; “Kappe-like” (potential or homologous “Kappe” as in teleosts), “pear-shaped” and “teardrop-shaped” cells. These morphotypes will need to be confirmed molecularly in the future. Using X-ray diffusible iodine-based contrast-enhanced computed tomography (diceCT), high-resolution scans of the olfactory rosettes, olfactory bulbs (OBs), peduncles, and telencephalon reveal a lateral segregation of primary olfactory inputs within the OBs, with distinct medial and lateral clusters of glomeruli, suggesting a potential somatotopic organization. However, most ORN morphotypes are found to be ubiquitously distributed within the medial and lateral regions of the olfactory rosette, with at least three microvilli-bearing ORNs labeled with anti-Gαo found in significantly higher densities in lateral lamellae [in lateral lamellae] and on the anterior portion of lamellae (facing the olfactory cavity). These microvilli-bearing ORN morphotypes (microvillous, “Kappe-like,” “pear-shaped,” and “teardrop-shaped”) are the most abundant across the olfactory rosette of this species, while ciliated ORNs are less common and crypt cells are rare. Spatial simulations of the fluid dynamics of the incurrent water flow into the nares and within the olfactory cavities indicate that the high densities of microvilli-bearing ORNs located within the lateral region of the rosette are important for sampling incoming odorants during swimming and may determine subsequent tracking behavior.